MODAL USAHA DAN KEMAMPUAN PETANI DALAM BUDIDAYA TANAMAN SELADA HIDROPONIK (STUDI KASUS HIDROPONIK NURI HORTI DAN HIDROPONIK FAPERTA DI KOTA KENDARI) - Lisa Erninda; Anas Nikoyan; Rosmawaty Rosmawaty (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
The objective of this study is to ascertain the business capital and capabilities of farmers in cultivating lettuce at Nuri Horti Hydroponics and Faperta Hydroponics in Kendari City. The informants in this study consisted of hydroponic business owners and farmers working at hydroponic business locations. The selection of informants was conducted using purposive sampling techniques, with the objective of identifying individuals who met specific criteria. This process resulted in a total of four research informants. The data presented herein was collected through a meticulous combination of observational studies, detailed documentation, and in-depth interviews conducted within a structured interview framework. The present study concentrated on the following subjects: business capital, farmers' capabilities, and hydroponic lettuce cultivation. The data were analyzed using qualitative descriptive methods. The results of the study indicate that the success of hydroponic lettuce cultivation at the two locations, namely Nuri Horti Hydroponics and Faperta Hydroponics, is supported by business capital sourced from personal savings and adequate technical and managerial skills of the farmers. Despite initial capital constraints, both business operators were able to manage the purchase of equipment and materials gradually and efficiently. From a technical perspective, farmers possess good knowledge and skills related to hydroponic systems, cultivation stages, and plant nutritional requirements, acquired through experience and self-directed training. Managerially, although they have not adopted modern management concepts, farmers have implemented simple yet effective planning, resource allocation, and business oversight. There are differences in cultivation approaches between the two locations: Nuri Horti Hydroponics directly transfers seedlings to the installation after germination, while Faperta Hydroponics uses a step-by-step process. These differences reflect the adaptation of methods based on the conditions and experiences of each entrepreneur. Hydroponic cultivation practices can succeed and develop even when conducted independently and with limited capital, provided that the operators possess sufficient technical skills and basic managerial capabilities. The adjustments made to cultivation methods based on individual experiences demonstrate the flexibility of the hydroponic system, which continues to prioritize principles of efficiency and sustainability.